PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Christyna Capriaty; Kenny Ardillah (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study examines the determinants of firm value among banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period by analyzing the roles of capital structure, dividend policy, firm size, and financial performance. A quantitative approach was employed using purposive sampling, resulting in 35 banking companies selected from a population of 48 firms based on the availability of complete annual financial reports throughout the observation period. Data analysis was conducted through classical assumption testing, hypothesis testing, and path analysis to evaluate direct and indirect relationships among variables. The findings indicate that dividend policy and firm size have a significant positive effect on financial performance, while capital structure has a significant negative effect. However, capital structure, dividend policy, and firm size do not directly influence firm value significantly. Conversely, financial performance has a significant positive impact on firm value, demonstrating its role as an important intervening variable in translating corporate strategies into market valuation. These results highlight that improving financial performance is a key mechanism for enhancing firm value, as investors primarily assess companies based on their operational effectiveness and financial achievements.